The Effect of Occupational Safety and Health (K3) Policy on Employee Performance - Sugiyanto Sugiyanto (LPPM of NAROTAMA UNIVERSITY, 2022)
Occupational safety and health policies differ from one company to another, depending on the level of concern of top management with protecting workers from hazards in the workplace. The purpose of this study was to determine the effect of occupational safety and health policies on employee performance in the company under study. Measurement of variables using a Likert scale with a scale of 1 to 5, to measure the attitudes, opinions and perceptions of workers about the implementation of the K3 program in their place of work. The technique of collecting data using a questionnaire method contains a number of questions distributed to workers (respondents). The results of the respondent's assessment were processed using the partial least square method. Based on the evaluation of the outer model, it shows that the indicators used to measure the latent variables (independent variables and dependent variables) have met the validity and reliability tests. Based on the inner model evaluation, it can be proven that there is a real correlation to employee performance, namely work environment 55%, employee competence 52%, top management commitment 47% and worker communication 39%. As for the K3 regulations and procedures as well as the involvement of workers, it was found quite small, respectively, 10% and 9% of the effect on employee performance and the magnitude of this influence was not significant.